Strategic agility and human resource management - Ahammad, Mohammad F. (2020)
This paper serves as an introduction to this special issue on strategic agility and human resource management. The paper starts with a summary review of the current state of the strategic agility literature followed by introduction of the five articles in the special issue. The paper also highlights the implications of the findings for academics and practitioners.